Health, Wellness, and Safety Aspects of the Consumption of Kombucha - Mindani I. Watawana; Nilakshi Jayawardena; Chaminie B. Gunawardhana; Viduranga Y. Waisundara (Journal of Chemistry)
Functional foods have been identified as whole foods and fortified, enriched, or enhanced products which have a potentially beneficial effect on health when consumed as part of a varied diet on a regular basis, at effective levels. As consumer awareness on functional food escalates, the interest towards conducting scientific studies in this field has also proportionately increased. Many of the traditional food products are known to possess bioactive components, thus qualifying as functional food. Kombucha tea is produced by fermenting sugared black tea with a mixed culture of yeast and bacteria. Kombucha tea has gained immense popularity in recent times due to many associated health benefits. The therapeutic effects of this beverage are thought to be derived from the chemical composition of this beverage, mainly the polyphenols and secondary metabolites which are produced during fermentation. However, the safety aspects of the beverage also need to be taken into account when qualifying the beverage as a functional food. Nevertheless, Kombucha tea could be easily recognized as a beverage which is able to replace the consumption of carbonated beverages due to its possession of health benefits and therapeutic properties.